Fabrication of Nanoscale Patternable Films of Silk Fibroin Using Benign Solvents. Issue 7 (20th April 2017) - Bucciarelli, Alessio; Pal, Ramendra K.; Maniglio, Devid; Quaranta, Alberto; Mulloni, Viviana; Motta, Antonella; Yadavalli, Vamsi K.
Abstract : Formic acid is presented as a sustainable solvent for silk fibroin and fibroin "resists, " for micro‐ and nanoscale applications such as next generation biocompatible optical devices. Mechanically robust, homogeneous, smooth, and transparent thin and ultrathin films are formed which can be used for high‐resolution photopatterning using benchtop lithographic techniques. Abstract : The silk protein fibroin is a wondrous biopolymer widely used to form structures that interface with biological entities. In addition to tissue scaffolds, sponges, and films, biochemically modified fibroins can be used in conjunction with techniques such as photolithography and soft lithography to expand their repertoire for micro‐ and nanofabricated systems. To date, the use of hexafluoro‐2‐isopropanol (HFIP) has been prevalent as a solvent for fibroin and fibroin "resists." However, high volatility, toxicity, cost, and need for specialized disposal render the necessity for alternative solvents. Additionally, for applications such as in optics and bioelectronics, smooth, thin (≈100 nm and below) fibroin films are a prerequisite, which are not easily achieved using HFIP. Here, the use of formic acid (FA) as a sustainable solvent is presented for silk fibroin and fibroin "resist" materials, specifically for micro‐ and nanoscale applications. The reproducible formation and characterization of stable thin films of high homogeneity, smoothness, and optical transparency are demonstrated. Critically, these films can be used for high‐resolution photopatterning of proteins using benchtop lithographic techniques. The study indicates that FA is a relatively benign and optimal solvent for forming smooth, thin films, and microscale architectures for the fabrication of next generation silk‐based optical devices.